Experiência turística de famílias com pessoas autistas - Amaral, Monica Santos Barbosa (2023)
Tourism is an experiential activity that can generate different emotions in tourists, some of which may be associated with the conditions experienced by travelers before and during the tour. In the case of people with autism spectrum disorder (ASD), a leisure trip can be considered a complex experience, as it involves routine changes and unpredictability. Understanding the tourist experience of families with autism is relevant for the consumer and tourism sectors. In this context, a qualitative research of the phenomenological type was carried out in this work. Episodic interviews were conducted with twelve mothers of autistic children and one hundred and forty-six photos were analyzed using the photo-elicitation technique. The set of information that constituted the corpus was interpreted from the pragmatic analysis of the direct type discourse. It was found that natural, built and cultural attractions, as well as social interaction and the price to visit the place, are common to any traveler profile. However, for mothers of autistic children, the tranquility of the place is fundamental due to their auditory and visual sensitivity and difficulties in social interaction. As for the mothers' expectations of taking a leisure trip, good and bad expectations were reported, however, uncertainty is something common among the interviewees. Because of this, mothers try to make predictions of what might happen and prepare to alleviate possible situations. Positive and negative emotions and feelings were reported, the positive ones being joy, gratitude, surprise, victory, joy, satisfaction and relief; and the negative ones, apprehension, nervousness, stress, anxiety, frustration, impotence, incapacity, insufficiency and failure. It was found that mothers consider tourist companies to be poorly prepared to receive different profiles of visitors. As there are several challenges during the tourist experience, traveling for these mothers means breaking barriers, achievements, evolution, learning, happiness, gratitude and memories of happy moments. This research contributes by showing that the tourist experience can be positive for mothers of autistic children, even in situations of unexpected behavior on the part of the child. But, for that, it is necessary that all the agents of the tourist activity are prepared to offer adequate environments and specialized service for these consumers